2022
DOI: 10.1136/ard-2022-223237
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of haemodynamic severity of systemic sclerosis-associated pulmonary arterial hypertension by serum proteome analysis

Abstract: ObjectivesTo mine the serum proteome of patients with systemic sclerosis-associated pulmonary arterial hypertension (SSc-PAH) and to detect biomarkers that may assist in earlier and more effective diagnosis and treatment.MethodsPatients with limited cutaneous SSc, no extensive interstitial lung disease and no PAH-specific therapy were included. They were classified as cases if they had PAH confirmed by right heart catheterisation (RHC) and serum collected on the same day as RHC; and as controls if they had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Serum anti-U11/U12 antibodies are strongly associated with moderate-to-severe gastrointestinal dysmotility [ 22 ]. For SSc-related PAH, it has been reported that serum levels of anti-centromere antibody (especially the anti-p4.2 antibody subset), anti-vinculin antibody, IL-32, midkine, follistatin-like 3, osteopontin, chemerin, and specific long noncoding RNAs (e.g., ANCR and SPRY4-IT1) are positively correlated with the presence of PAH, whereas serum anti-topoisomerase antibody levels are negatively correlated with the presence of PAH [ 23 30 ]. In this microarray study, we identified 125 serum protein biomarkers in different pulmonary complication subgroups of patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Serum anti-U11/U12 antibodies are strongly associated with moderate-to-severe gastrointestinal dysmotility [ 22 ]. For SSc-related PAH, it has been reported that serum levels of anti-centromere antibody (especially the anti-p4.2 antibody subset), anti-vinculin antibody, IL-32, midkine, follistatin-like 3, osteopontin, chemerin, and specific long noncoding RNAs (e.g., ANCR and SPRY4-IT1) are positively correlated with the presence of PAH, whereas serum anti-topoisomerase antibody levels are negatively correlated with the presence of PAH [ 23 30 ]. In this microarray study, we identified 125 serum protein biomarkers in different pulmonary complication subgroups of patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Piera-Velazquez and Colleagues elegantly demonstrated that proteomic analysis of serum exosomes differs between patients with primary Raynaud’s phenomenon and patients with Raynaud’s phenomenon at risk of evolving into SSc ( 39 ). In the other two studies available ( 37 , 38 ), the aptamer analysis was applied to describe longitudinal changes in patients with established SSc and organ damage. It was indeed demonstrated that serum levels of ST2 and spondin-1 predicted the changes in mRSS, also providing evidence of a peculiar cytokine signature (i.e., TNF, IFN-γ, TGF-β, and IL-13) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was indeed demonstrated that serum levels of ST2 and spondin-1 predicted the changes in mRSS, also providing evidence of a peculiar cytokine signature (i.e., TNF, IFN-γ, TGF-β, and IL-13) ( 37 ). Additionally, chemerin was identified as a potential biomarker with pathogenic significance for increased pulmonary vascular resistances in patients with SSc-PAH ( 38 ). In another study, 82 proteins were found to be differentially expressed in sera from SSc-PAH patients compared to SSc patients without lung vascular involvement, including an IFN-γ signature and two other proteins of interest, Midkine (implicated in the pathogenesis of arterial hypertension, renal disease, and lung fibrosis) and Follistatin-like 3 (FSTL3, regulated by TGF-β) in association with SSc-PAH ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a proteome analysis was performed on the sera of 31 lcSSc patients (15 with PAH and 16 without PAH) in order to identify a valid biomarker of lcSSc-associated PAH; patients with extensive ILD or who had already been treated for PAH were excluded. Serum levels of chemerin, a pleiotropic protein that exerts its multiple effects on SMCs, inducing their contraction and proliferation, and on endothelial cells, regulating neoangiogenesis, NO production and cell adhesion, were found to be higher in lcSSc patients with PAH vs. in those without it; moreover, in lcSSc-PAH patients, chemerin levels appeared to correlate with PVR, performing as a marker of haemodynamic severity in these patients [ 60 ].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%